Host FIH-Mediated Asparaginyl Hydroxylation of Translocated Legionella pneumophila Effectors - Price, Christopher; Merchant, Michael; Jones, Snake; Best, Ashley; Von Dwingelo, Juanita; Lawrenz, Matthew B.; Alam, Nawsad; Schueler-Furman, Ora; Kwaik, Yousef A. (Frontiers in Cellular and Infection Microbiology, 2017)
FIH-mediated post-translational modification through asparaginyl hydroxylation of eukaryotic proteins impacts regulation of protein-protein interaction. We have identified the FIH recognition motif in eleven Legionella pneumophila translocated effectors, YopM of Yersinia, IpaH4.5 of Shigella and an ankyrin protein of Rickettsia. Mass spectrometry analyses of the AnkB and AnkH effectors of L. pneumophila confirm their asparaginyl hydroxylation. Consistent with localization of the AnkB effector to the Legionella-containing vacuole (LCV) membrane and its modification by FIH, our data show that FIH and its two interacting proteins, Mint3 and MT1-MMP are acquired by the LCV in a Dot/Icm type IV secretion-dependent manner. Chemical inhibition or RNAi-mediated knockdown of FIH promotes LCV-lysosomes fusion, diminishes decoration of the LCV with polyubiquitinated proteins, and abolishes intra-vacuolar replication of L. pneumophila. These data show acquisition of the host FIH by a pathogen-containing vacuole and that asparaginyl-hydroxylation of translocated effectors is indispensable for their function.